2019
DOI: 10.3390/sports7040091
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effect is Modulated by Playing Position but is Not Related to Competitive Success in Elite Under-19 Handball Athletes

Abstract: This study aimed to verify the occurrence of the relative age effect (RAE) in male elite young handball athletes according to the playing position and its association with team performance in a World Championship. Data from 383 handball athletes from 24 countries who participated in the 7th World Men’s Championship in the under-19 category were analyzed. RAE was investigated from the birth trimester of the athletes, their playing position, and final ranking in the Championship. The results showed an overrepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 46 publications
9
38
1
2
Order By: Relevance
“…These results are in accordance with other sports, such as handball [41] where no relationship was demonstrated between the chronological age of the athletes and the team's success. However, in other studies, the play position and team performance were affected by the RAE [42].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in accordance with other sports, such as handball [41] where no relationship was demonstrated between the chronological age of the athletes and the team's success. However, in other studies, the play position and team performance were affected by the RAE [42].…”
Section: Discussionsupporting
confidence: 90%
“…Our handball youths showed similar results to their non-elite players in anthropometrical parameters such as height, weight, fat percentage, and arm span, with our results being slightly below their elite youth [13,16]. Specifically, they found a direct relationship between biological maturation and all anthropometrical characteristics except body fat, and two more studies [25,26] verified this relative age-dependent effect in young elite handball athletes. In our study, when analyzing body composition by categories and after age adjustment, we observed that many of the differences disappeared, except for lean mass.…”
Section: Discussionsupporting
confidence: 78%
“…Anthropometric and physical requirements in handball, such as the need to have a large and strong body, high strength levels, and a high throwing velocity [56][57][58], mean that relatively older players tend to be in back positions, compared to relatively young players [59]. Unlike previous studies of male handball players that also included an analysis of playing positions [28,39], we found a higher prevalence of the RAE on the selection of athletes to the positions of pivots and goalkeepers. Large anthropometric size and strong physical capacities are required to compete in elite handball in general, and in goalkeeper and pivot positions in particular [60], but it seems that position-specific skill demands may also explain the RAE on these two playing positions [61].…”
Section: Plos Onementioning
confidence: 99%
“…Only one study has compared the impact of the RAE in different countries. In a study of athletes selected to international youth competitions in handball, Fonseca et al [28] included 383 youth male handball players from the 24 countries participating in the 7 th Men's Youth World Championship held in 2017. Findings showed the prevalence of the RAE in the population sample but found no relationship between the age of the players and the success of each team-measured as a team´s championship ranking.…”
Section: Introductionmentioning
confidence: 99%